AB0608 Clinical profile of filipino paediatric patients with systemic lupus erythematosus. (12th June 2018) - Santiago, A.-T.M.; Tee, M.; Tee, C.
Abstract : Background: The clinical profile of paediatric SLE patients may present differently from that of adults. Objectives: To determine the clinical profile of Filipino paediatric SLE patients as determined using the 2012 Systemic Lupus Collaborating Clinics (SLICC) criteria. Methods: We checked which among the SLICC criteria were fulfilled by Filipino paediatric SLE patient when we examined them and their case records, as part of a nationwide genetic study on SLE conducted from October 2015 to March 2017. Results: Ninety-eight who were diagnosed to have SLE before 18 years of age were evaluated. The mean age of the population at the time of evaluation was 19.77 years. Females comprised 94% of our population. Mean age of onset was 14.42-year-old, while the mean age of diagnosis was at 14.58-year-old. Acute cutaneous rash was found in 87%; oral ulcers 65%; renal disorder 65%; non-scarring alopecia 61%; arthritis 58%; chronic cutaneous rash in 37%; leukopenia 36%; hemolytic anaemia 34%; serositis 24%; thrombocytopenia 22% and neurologic disorder 8%. Anti-nuclear antibody was present in 88%; low complement 33%; anti-dsDNA in 28%; direct Coombs' 16%; antiphospholipid antibody 3%; and anti-Smith antibody in 1%. Kidney biopsy was performed in only 14% (15/104) of patients, of whom 27% had class III histopathologic characteristic. Conclusions: Filipino paediatric SLE patients typically present with cutaneous, mucocutaneous renal and musculoskeletal involvement. Hematologic and neurologic manifestations are found to be less common among them. Finally, it was noted that renal biopsy is not commonly performed among these patients. Disclosure of Interest: None declared